Spawning season of milkfish \(Chanos chanos\) (Forsskål, 1775) in the nature - Ta , Thi Binh; Tran , Thi Kim Ngan; Nguyen , Dinh Vinh; Le , Phuong Nam; Nguyen, Minh Tam; Nguyen , Xuan Truong (Academia Journal of Biology, 2023)
The spawning season of the milkfish Chanos chanos (Forsskål, 1775) of the family Chanidae in the Central Coast of Vietnam was determined. A total of 220 specimens (3.20 to 4.50 g body weight, BW) was collected from seven provinces (Nghe An, Ha Tinh, Quang Binh, Quang Tri, Binh Dinh, Khanh Hoa, Ninh Thuan) from January to December 2021. Results showed that the Gonado Somatic Index (GSI) ranged from 2.03 to 16.02 in females and 1.15 to 9.87 in males and had two peaks, one in April–May (13.47–16.02 for females and 8.03–9.87 for males) and another in August-September (11.45–12.32 for females and 6.75–7.98 for males). Conditional factors in females and males ranged from 3.68×10-2 to 4.11×10-2 and 3.02×10-2 to 3.43×10-2, respectively with the highest values found in May (4.11×10-2 for females and 3.46×10-2 for males) and September (3.92×10-2 for females and 3.34×10-2 for males). The Fulton’s and Clark’s indexes were highest in November, 1.82% and 1.67%, respectively and these were then decreased in the following months; the lowest values were recorded between August to September and April to June (0.66–0.74% Fulton and 0.49–0.72 Clark). The gonadal development stages III and IV in females and males were observed from April to June and August to September of the year. Our findings suggest that the main spawning seasons of milkfish take place from April to June and August to September.